Effectiveness of ethics case based on blended learning approaches on medical students' learning: A quasi-experimental study - Atefeh Karamzadeh; Leili Mosalanejad; Leila Bazrafkan (Wolters Kluwer Medknow Publications, 2021)
BACKGROUND: The use of active teaching methods in ethics education, instead of being merely teacher centred, can lead students to problem-solving in a practical way. Therefore, this study was conducted with the aim of comprehensive medical ethics education based on educational approaches and the effect of this approach on students' learning and moral reasoning skills. MATERIALS AND METHODS: This quasi-experimental intervention study was performed on seventy physiopathology medical students who had taken the medical ethics course. The students' educational program included teaching theoretical concept of medical ethics, discussing ethical cases and clinical reasoning in class, and then discussing in forum environment and individual assignments in the learning management system (LMS) system and completing the portfolio. Student evaluation was associated students' knowledge, attitu de, and moral reasoning skills and learning. A comprehensive program including forum participation, individual assignments in LMS, theory and objective structured clinical examination (OSCE) tests, and portfolio completion was used to evaluation of students. The students' learning was compared to students of the previous year, which was conducted through a traditional teacher-centered method. Data analysis was conducted using IBM® SPSS® Statistics 21 at two levels of descriptive statistics and analytic statistics. RESULTS: The results showed that there was a significant difference between the mean learning of students compared with traditional class (P < 0.05). Furthermore, comparison of students' practical scores through the OSCE test showed its impact on changing students' knowledge, attitude, and performance in moral reasoning. CONCLUSION: According to research findings, it seems that the mentioned model is one of the important and new issues as a suitable method of teaching medical ethics. Furthermore, it can be suitable model in other medical courses. The more research in multicentral may be need to assess other effects on students' learning indicators.